Preliminary work on molecular identification of markers linked to papaya sex gene locus - Lee, Jenny (Universiti Malaysia Sarawak (UNIMAS), 2006)
Carica papaya is a polygamous plant species with male, female and hermaphrodite sexes. Genetic studies have shown that sex in papaya is controlled by a major gene SexI with three alleles. However, the sex of the plant can not be identified through morphological characteristics. Since only the fruits from hermaphrodite plants are in greater demand and the female plants can only be rouged out after reaching the flowering stage, development of a molecular marker would be usefu'l to papaya growers. The objective of this project is to identify any diagnostic bands that are linked to papaya sex determination gene. In this study, both female and hermaphrodite leaf samples of Sekaki cultivar were collected for analysis. The genomic DNA was successfully isolated from papaya leaves using the modified CT AB method. DAMD-PCR technique was used to detect any sex-specific patterns. Limited polymorphic banding profiles for female and hermaphrodite samples were generated using MI3 universal primer in this study. However, no diagnostic band was detected.